Levantamento de manifestações patológicas em igreja do município de Jaboticabal - SP - Panosso, Mayara Aparecida (2023)
Pathological manifestations affect the visual appearance and durability of constructions. The study of these anomalies in cultural and religious heritage is crucial due to their historical and cultural importance. The present study aims to carry out a survey of pathological manifestations on the facades of the São Benedito church, located in the city of Jaboticabal - SP. The identification of these anomalies was carried out based on images obtained with a photographic camera and registered in a specific spreadsheet, being analyzed: cracks and cracks, efflorescence, disintegration, mold and mildew, dirtiness, bubbles or vesicles and, presence of vegetation, with the respective location on the façade: base, central, superior and frames. A sketch of each face of the building was prepared in order to identify and locate the pathologies, that is, the representation through the damage map. The study of the building's facades revealed a series of pathologies that require attention and corrective action. The northeast, southwest, southeast and northwest facades show cracks, disintegration, presence of mold and mildew, dirt and vegetation. These pathologies may indicate structural problems, lack of proper maintenance, humidity and lack of ventilation. In addition to compromising the aesthetics of the facades, these conditions can cause damage to building materials and pose risks to the integrity and safety of the building. It is concluded that the study of pathological manifestations in buildings, especially in cultural and religious heritage, is essential to preserve their history and cultural value. By identifying and understanding these anomalies, we can take corrective measures and improve the conservation of these assets, ensuring their long-term sustainability and relevance.